Peranan New Media Dalam Transformasi Fungsi Komunikator Dan Fungsi Konstruksi (Dramaturgy Akun Instagram Walikota Denpasar Rai Mantra Tahun 2019) - I Gede Titah Pratyaksa; Ni Luh Wiwik Eka Putri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
New Media helps in providing unlimited information to the public. The public in other places can receive the message quickly and intact, to then package the feedback and send it back. New media in this case Instagram social media has transformed the function or role of communicators and communicants. Communication through social media Instagram conducted by the Mayor of Denpasar, Ida Bagus Rai Dharmawijaya Mantra in developing personal branding is fairly effective and efficient. This is one of the right strategies in the face of the industrial revolution 4.0. The author classifies the photos on Rai Mantra's Instagram account into several categories, namely social, security, political, economic, and personal. Rai Mantra's Instagram account can answer aspects of who, where, when, how and why an action is taken in their daily activities. In pentad drama, which are act, scene, agent, agency, purpose.